(untitled) (ZOO-Journal, 2019)
This study was carried out to determine the prevalence of intestinal parasitic infections among the children of age group 4-12 years in Bheerkot Municipality of Syangja District, Nepal, at an altitude of 1088 m above sea level. The research was conducted among 50 children i.e., 24.27% of total children population of that age group. Among 50, 21 (42%) and 29 (58%) were male and female respectively, on which parasitic infection was observed in 42.85% of male population and 31.03% of female population, but there was no association of gender for the infections of intestinal parasites. This indicates that the association of gender with intestinal parasitic infection differs from one community to other and might be attributed to socio-behavioral activities. The samples were examined under optical microscope (low power-10X and high power 40X). The major intestinal parasites detected were Giardia lamblia (Lambl), Entamoeaba histolytica (Schaudinn), Entamoeba coli (Grassi) and Trichuris trichiura (Linnaeus). In conclusion, among above mentioned parasites, Giardia lamblia was found with higher prevalence infecting 16 of total children, we recommend for improvement in the drinking water habit and proper sanitation in the people of Bheerkot-3 and need of effective social awareness programs